Linfopenia y riesgo de infecciones nosocomiales en ancianos en una institución de salud de Bogotá, Colombia. Estudio de casos y controles - Carlos José Ariza-Galindo (Asociación Colombiana de Infectología, 2020)
Objective: Lymphopenia has been proposed as a potential factor associated with the risk of nosocomial bacterial infections (urinary tract infection and pneumonia),but the magnitude and relevance of this factor has not been formally evaluated. Objective is to determine the association between lymphopenia and nosocomial infections in elderly hospitalized in a health institution in Bogotá, Colombia. Methods: Case-control study, including people over 65 hospitalized in the University Hospital San Ignacio - Bogotá, during the period between June 2016 and December 2017. Cases with a diagnosis of nosocomial infection (pneumonia, urinary tract infection, bacteraemia, soft tissue infection) were considered and compared with controls without infection matched by age and sex. The association between lymphopenia and nosocomial infection was evaluated by bivariate and multivariate analysis, controlling for confounding variables. Results: A total of 198 patients (99 cases and 99 controls) were included. The prevalence of lymphopenia was 34.8%, with no difference between the two groups (p = 0.88). Nosocomial infection was associated with a higher incidence of mortality (29.3 vs. 10.1%, p> 0.001) and a longer duration of hospital stay (Median 18 vs. 9 days, p <0.01). An association was found between nosocomial infection with cardiovascular disease (OR = 2.87; 95% CI 1.37-6.00) and a history of cancer (OR = 6.19; 95% CI 1.28-29.78), however, there was no association with lymphopenia (OR = 1.27 ; 95% CI 0.61-2.65). Conclusions: This study suggests that there is no association between lymphopenia and the development of nosocomial infections in elderly patients.